Contending With Defense Industry Reallocations: A Literature Review of Relevant Factors. (November 2017) - Zullo, Roland; Liu, Yijun
The authors review research on the destabilizing effects of defense department reallocations at the firm and community levels, with the intent to inform current intervention policy for assisting firms and regions dependent on defense spending and to lay the groundwork for evaluative research. The existing literature provides at least 10 firm-level and 7 community-level factors affecting economic stabilization following a loss in defense industry dollars. The 10 microlevel factors are product specialization, product technology, industry condition, new market target, civilian market experience, firm size, location and status in the network, workforce skills, operational assets, and personnel policy. The seven meso level factors are economic integration, urbanization, economic diversity, health of local economy, local demand for workforce skill, capital asset utilization, and land use policy.